2019
DOI: 10.1002/qj.3519
|View full text |Cite
|
Sign up to set email alerts
|

The impact of spin‐up and resolution on the representation of a clear convective boundary layer over London in order 100 m grid‐length versions of the Met Office Unified Model

Abstract: With a number of operational centres looking forward to the possibilities of “city scale” NWP and climate modelling it is important to understand the behaviour of order 100 m models over cities. A key issue is how to handle the representation of partially resolved turbulence in these models. In this article we compare the representation of a clear convective boundary‐layer case in London in 100 and 50 m grid‐length versions of the Unified Model (MetUM) with observations. Comparison of Doppler lidar observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(51 citation statements)
references
References 55 publications
1
50
0
Order By: Relevance
“…Lean et al . (2019) also ran MetUM with 100‐m grid length for a domain size of 80 × 80 km 2 and 30 × 30 km 2 , similar to the two domain sizes used in our sensitivity experiments. They found that it was necessary to use a larger domain to avoid spin‐up effects penetrating into the area of interest in clear‐sky convective boundary‐layer situations.…”
Section: Resultsmentioning
confidence: 99%
“…Lean et al . (2019) also ran MetUM with 100‐m grid length for a domain size of 80 × 80 km 2 and 30 × 30 km 2 , similar to the two domain sizes used in our sensitivity experiments. They found that it was necessary to use a larger domain to avoid spin‐up effects penetrating into the area of interest in clear‐sky convective boundary‐layer situations.…”
Section: Resultsmentioning
confidence: 99%
“…For UK applications, it also has to be considered that the empirical relations were derived for ∼1-km NWP applications, and it is unclear whether they are still appropriate at much higher or lower resolutions. Over London, the UKV is currently run routinely at ∼300-m horizontal resolution, and with even higher resolved simulations being used (∼50-100 m; Lean et al 2019) the derivation of morphology ancillaries should be revisited and evaluated. Using a representative canyon proportion (W/R) in MORUSES can strongly affect model behaviour and hence is important for NWP and climate modelling.…”
Section: Discussionmentioning
confidence: 99%
“…Computing advances are making it possible to have focused grids in the 100-300 m scale over small regions of interest, such as urban areas. For example, the United Kingdom's Met Office is using a 100 m grid domain over London (Lean et al 2019), and Environment and Climate Change Canada has tested 250 m over Vancouver (Leroyer et al 2014). However, such models remain in the gray zone where large turbulent eddies are resolved but smaller ones are not, and where the heterogeneity and complexities of the surface topography and the urban built surface are at scales comparable to the grid scale.…”
Section: Multiscale Ensemble Prediction: Challenges and Suggested Focimentioning
confidence: 99%